2013
DOI: 10.5433/1679-0359.2013v34n3p1381-1388
|View full text |Cite
|
Sign up to set email alerts
|

Complexo enzimático na dieta de alevinos de kinguio (Carassius auratus)

Abstract: ResumoObjetivando avaliar a suplementação de complexo enzimático em dietas de alevinos de kinguios (Carassius auratus), foram utilizados 240 peixes com peso inicial de 1,36 ± 0,02g, distribuídos aleatoriamente, em 20 tanques de 150L, em quatro tratamentos e cinco repetições, com 12 peixes em cada unidade experimental. Os peixes foram arraçoados as 8h, 11h, 14h e 17h, com dietas contendo diferentes níveis de inclusão (0; 0,033; 0,066 e 0,099%) de complexo enzimático (amilase, protease, celulase, lipase, b-gluca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…As observed, the data found in the literature are controversial. Such a divergence in results may be related to the level of inclusion of the enzymes in the diets, the structure of the enzymes present in the ingredients, the type of diet (live food and dry diets), the different types of enzymatic products, the different temperatures used in the formulation of the diet, the various species, as well as the ability of each species to adapt its digestive tract to the ingredient or their food preference, resulting in differences in the zootechnical performances and intestinal villi of the animals (Leenhouwers, Ter Veld, Verreth, & Schrama, ; Signor et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed, the data found in the literature are controversial. Such a divergence in results may be related to the level of inclusion of the enzymes in the diets, the structure of the enzymes present in the ingredients, the type of diet (live food and dry diets), the different types of enzymatic products, the different temperatures used in the formulation of the diet, the various species, as well as the ability of each species to adapt its digestive tract to the ingredient or their food preference, resulting in differences in the zootechnical performances and intestinal villi of the animals (Leenhouwers, Ter Veld, Verreth, & Schrama, ; Signor et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of digestive enzyme supplementation has been a common practice in poultry and pig feeding (Bedford, ), but in fish, this technique is not widely applied due to technological difficulties during pelletizing and extrusion processes, which involves high temperature levels and low stability to heat of enzymes (Mascarell & Ryan, ). Although several studies have demonstrated that the addition of exogenous digestive enzymes in the diet did not affect the survival and growth of several fish such as European sea bass larvae ( Dicentrarchus labrax ), juveniles of Nile tilapia ( Oreochromis niloticus ) (Signor et al, ), kinguio ( Carium auratus ) (Signor et al, ) and common carp ( Cyprinus carpio ) (Kazerani & Shahsavani, ), other studies have found positive results.…”
Section: Introductionmentioning
confidence: 99%
“…Signor et al (2013), ao avaliarem a suplementação com complexo enzimático (amilase, protease, celulase, lipase, b-glucanase e fitase) em rações para o peixes ornamental japonês (Carassius auratus), não observaram diferenças significativas para o crescimento, ganho em peso e conversão alimentar. Igualmente, Kazerani e Shahsavani (2011) avaliando a inclusão de um complexo enzimático em dietas a base de farelo de trigo, soja e farelo de algodão, em rações para carpa (Cyprinus carpio) os autores verificaram que a inclusão do complexo não foi eficiente em proporcionar uma melhor conversão alimentar, crescimento e ganho em peso, apresentando resultados inferiores aos da dieta controle, quando adicionadas em excesso.…”
Section: Resultados Da Adição De Enzimas Na Nutrição De Peixesunclassified